Internationalization of higher education in Vietnam: new policies needed for new context - Nguyễn, Thùy Anh (International school. Vietnam national university, Hanoi, 2020)
Over the past decades, internationalization of higher education has accelerated in terms of both pace and magnitude, having impact on countries and institutions the world around. Since its start of Doimoi policy in 1986, Vietnam has achieved remarkable development in higher education. However, it is still faced with serious chronic and emerging problems. Internationalization of higher education is therefore considered as one of the necessary solutions for Vietnam and its institutions to enhance educational quality and thus catch up with regional and international standards. The purpose of the paper is to investigate the policies for and current status of internationalization of higher education in Vietnam. The paper will first analyze the legal and policy framework for Vietnam’s internationalization of higher education. Second, it will examine how this process is being implemented at the national level. Finally, the paper will discuss issues and challenges that Vietnam has to face with during the process of higher education internationalization. Data and information used to analyze in this paper were collected by the author from various sources such as the Ministry of Education and Training (MOET), the UNESCO Institute for Statistics and the Institute for International Education (HE). The paper therefore provides an insightful and comprehensive understanding of the current situation of higher education internationalization in Vietnam with a variety of facts and figures, highlighting its problems and challenges in this process and contributing to literature on this issue in Vietnam.